2018
DOI: 10.1016/j.ijnurstu.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cooling therapy (cryotherapy) on leg pain and self-efficacy in patients with chronic venous disease: A randomized controlled trial

Abstract: Pain was reduced in both groups while self-efficacy did not change. Findings suggest that strictly implemented standard of CVeD care in each study group, with or without cooling, improved pain while there were no effects on self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…It is difficult to draw a solidified conclusion on chronic venous disease and MS due to lack of studies in the literature. The one study we found on chronic venous disease, conducted by Kelechi et al, reported a reduction in both long-term (measured by Venous Insufficiency Epidemiological and Economic Study-Quality of Life/Symptoms, VEINES-QOL/Sym) and short-term pain (measured by the Numeric Rating Scale, NRS) in the group that received cryocuff therapy as well as the placebo group that received a cotton-filled cuff, with no significant differences between groups [44]. Since there were no differences between groups, it could be plausible that the compression from the cryocuff had an impact on pain rather than the cold therapy itself.…”
Section: Othermentioning
confidence: 72%
“…It is difficult to draw a solidified conclusion on chronic venous disease and MS due to lack of studies in the literature. The one study we found on chronic venous disease, conducted by Kelechi et al, reported a reduction in both long-term (measured by Venous Insufficiency Epidemiological and Economic Study-Quality of Life/Symptoms, VEINES-QOL/Sym) and short-term pain (measured by the Numeric Rating Scale, NRS) in the group that received cryocuff therapy as well as the placebo group that received a cotton-filled cuff, with no significant differences between groups [44]. Since there were no differences between groups, it could be plausible that the compression from the cryocuff had an impact on pain rather than the cold therapy itself.…”
Section: Othermentioning
confidence: 72%
“…No statistically significant differences in scores at baseline, nor differences in change from baseline to the end of study were observed between groups; however, both groups experienced statistically significant decreases in mean pain scores (Δ =−1.5, P <.001; Δ =−1.7, P <.001 respectively). (20)…”
Section: Discussionmentioning
confidence: 99%
“…It is a widely held belief that the sensory neuropathy that often accompanies foot ulcers leads to an “insensate” foot; paradoxically, pain is present in up to 75% of individuals with diabetes-related foot ulcers 12. Pain and other uncomfortable symptoms such as itch, tingling, and achiness are also prevalent in patients with healed ulcers 13. Research also shows a high number of individuals with VLUs and DFUs are physically deconditioned, less physically active, have poor balance and gait abnormalities, and are slower walkers 14,15.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 There are also benefits in reducing pain through affecting nociceptor function and slowing nerve transmission velocity in pain fibers. 13,25 Pain, in particular, is known to negatively influence physical activity in patients with chronic venous disease. 26 In an attempt to address pain and physical activity, we developed a topically applied cooling patch as part of our MUSTCOOL intervention and posited that if pain was reduced, individuals would feel better and become more physically active.…”
Section: Introductionmentioning
confidence: 99%